Pengaruh Pemberian Pupuk Posfor Terhadap Pertumbuhan Beberapa Varietas Kedelai(Glycine max (L.)Merril) - Shandy Kurniawan; Aslim Rasyad; Wardati ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
ABSTRACT This research  was intended to determine the effect of three rates of phosphorous (P) on crop growthof  several varieties of soybean. A field experimentwas conducted at the Faculty of Agriculture, University of Riauexperiment station in Pekanbaru fromApril to August 2013. Four soybean varieties were grown and fertilized with three rates of Pfertilizer;  ie 0 kg, 25 kg, and 50 kg P2O5/ hectare. Each varieties were theplanted in a plot of 3.2 m by 3 m with planting rate of 40 cm between rows and 15 cm within a row.  Fertilizer including 50 kg N, 30 kg K2O per hectars and P fertilizer according to assigned treatment were applied seven days after planting. Traits observed were plant height, crop growth rate,crown root ratio, time to flowering, timetoharvest, number of filled pods per plant , number of seeds per plant, seed weight per plant and grain yield per m2.Data were analyzed by analysis of variance and further tested by least significantdifference at 5% level . This research indcated the differences among varieties on all traits except on root nodule weight and grain weight per plant.There were same differences among varieties on their respons to P fertilizer  as shown by all ofthe observation except  for number of filled pods per plant.  Specifically grain yield increased by aplication of P fertilizer on Grobogan and Argomulyo, however for  Anjasmoro and Burangrang, aplication of P fertilizer tent to reduced grain yield. Keywords : varieties, phosphorus, soybean ( Glycine max(L.) Merrill)